1993
DOI: 10.1136/gut.34.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Lower oesophageal sphincter hypersensitivity to opioid receptor stimulation in patients with idiopathic achalasia.

Abstract: Impairment of non-cholinergic innervation of the lower oesophageal sphincter has been suggested in idiopathic achalasia. As opioid nerves are present in the lower oesophageal sphincter and opioid peptides affect lower oesophageal sphincter motility, the effect of an opioid agonist, morphine (100 ,uggkg iv), and an opioid blocker, naloxone (80 ,ug/kg iv), on lower oesophageal sphincter motor function was assessed in 10 healthy subjects and in 10 patients with untreated idiopathic achalasia on separate days and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…impairment of inhibitory neural pathways due to degeneration of inhibitory ganglion cells in the myenteric plexus of the oesophagus and degenerative lesions in the vagal nerves and the dorsal motor nucleus). 5,[13][14][15][16] Studying oesophageal motility induced by rapid air infusion poses a few challenges in these patients before miotomy or pneumatic dilation is performed. On one hand, the oesophageal body is variably dilated before treatment, making it difficult to standardize distending stimuli; on the other, traditional quantitative variables of motility (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…impairment of inhibitory neural pathways due to degeneration of inhibitory ganglion cells in the myenteric plexus of the oesophagus and degenerative lesions in the vagal nerves and the dorsal motor nucleus). 5,[13][14][15][16] Studying oesophageal motility induced by rapid air infusion poses a few challenges in these patients before miotomy or pneumatic dilation is performed. On one hand, the oesophageal body is variably dilated before treatment, making it difficult to standardize distending stimuli; on the other, traditional quantitative variables of motility (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although the effects of gluten exorphins still remain to be fully elucidated, it could be argued that the gluten exorphins, opioid peptides identified in the enzymatic digests of gluten, could exert a morphine‐like activity on esophageal and gastric motility. However the motor effects of the morphine on gastroesophageal motility seem contradictory, as in fact while some authors described that morphine induces lower esophageal sphincter (LES) relaxation, decreases the resting LES pressure, 16 delays gastric emptying 17 —factors that could be involved in gastroesophageal reflux—others have suggested that morphine decreasing gastric fundal volume could decrease transient LES relaxation and gastroesophageal reflux 18 …”
Section: Discussionmentioning
confidence: 99%
“…Resting LES pressure is decreased both in health and in achalasia; swallow-induced LES relaxation is also significantly decreased by morphine in the healthy subjects. 39 A range of manometric abnormalities have been reported in patients with dysphagia using chronic opioids, such as impaired LES relaxation, high amplitude/velocity and simultaneous esophageal waves, 40 as well as esophagogastric junction outflow obstruction, higher integrated relaxation pressure, and lower distal latency on esophageal pressure topography. 41 Some of these findings are in contrast to the acute opioid effects cited previously.…”
Section: μ Opioids Gi Symptoms and Syndromesmentioning
confidence: 99%
“…Two studies have demonstrated an acute decrease in lower esophageal sphincter pressure by μ opioid receptor stimulation. 28,29 Nevertheless, the sum of these motor and secretory effects result in anorexia, nausea, emesis, impaired ability to evacuate the bowel, as well as abdominal spasm, cramps, and pain. 19,30 Decreased gastric, biliary, pancreatic and intestinal secretions interfere with digestion.…”
Section: Introductionmentioning
confidence: 99%